Du paternalisme industriel des company towns à la politique de Responsabilité Sociale des Entreprises Le cas de La Oroya (Pérou) - Claude Le Gouill (Caravelle)
While Latin America got involved in an outbreak of new conflicts between mining enterprises and rural communities since the last years of the 1990s, we propose an analysis of mining capitalism’s evolution based upon a historical zone of production: the Company town of La Oroya in Peru. This is an emblematic case of capitalism’s evolutions from 20th century paternalism to politics of Enterprises’ Social Responsiblities, including the 21st century’s new environmental issues.